Historical Context about The Impact of Accounting Principles of ‎Greek Enterprises - Challoumis, Constantinos; Eriotis , Nikolaos; Vasiliou , Dimitrios (International Journal of Accounting and Economics Studies, 2025)
This study examines the historical development, implementation, and impact of accounting principles on Greek enterprises, highlighting the ‎interplay between national regulations, European Union directives, and international standards. It traces the evolution of accounting in ‎Greece from the dominance of Law 2190/1920 and tax-based reporting to the gradual adoption of International Financial Reporting Standards (IFRS) after EU Regulation 1606/2002. The analysis demonstrates how accounting principles—ranging from conventional frameworks to IFRS—have influenced financial transparency, taxation practices, corporate governance, and decision-making processes in Greek ‎enterprises. Particular emphasis is placed on the role of taxation, sector-specific challenges in tourism and shipping, the contribution of professional accountants, and the adoption of technological advancements in accounting. Comparative insights with other EU countries reveal ‎both similarities and persistent divergences in practice. The study concludes that while IFRS adoption has enhanced transparency and confidence, Greek enterprises continue to face challenges in aligning local tax-oriented practices with international reporting requirements. ‎Policy recommendations underscore the need for harmonization, continuous professional development, and sector-adjusted approaches to ‎strengthen the effectiveness of accounting as a tool for governance, decision-making, and economic resilience in Greece‎.